Analisis Postur Kerja Metode Reba pada Pekerja Sentra Industri Perkayuan - Prasetyo, Rian (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2024)
Balepanjang is one of the Village in Wonogiri Regency is the center of the wood processing industry. From observations in the field the workers when doing work activities are not very ergonomic. Where standing is too bent, legs too bent, and sitting is not in accordance with the posture. If left unchecked, it can cause work-related injuries and illnesses, then a work posture analysis is carried out to determine the level of risk that workers may experience. This study aims to evaluate the work posture of the workers in the wood industry center in Balepanjang Village, Jatipurno District, Wonogiri Regency with the REBA (Rapid Entire Body Assessment) method to minimize the occurrence of work-related injuries and illnesses in workers. based on the results of measuring work postures using the REBA method, it was found that the process of lifting wood and pushing it to the saw machine in the home sawmill industry, a REBA score of 10 was in the high level category.